Analysis of the Role of State Administrative Law in Public Policy - Ni Putu Suryantari; Desak Putu Dewi Kasih (West Science Interdisciplinary Studies, 2025)
State Administrative Law has a very important role in the formation, implementation and supervision of public policy in a country. This law regulates the relationship between state institutions and society, and provides a valid legal basis for government actions. This research aims to analyze the role of State Administrative Law in public policy, especially in terms of transparency, accountability and equity in public services. The method used in this research is a normative research method where this research was carried out based on secondary data in the research. The type of approach used is a qualitative approach with descriptive analysis. The research results show that State Administrative Law plays an important role as a legal basis in the preparation and implementation of public policies. HAN ensures that the policies taken by the government are in accordance with applicable laws and regulations, prevent abuse of authority, and guarantee justice for the community. Oversight and accountability in public policy, through supervisory institutions and administrative justice, ensure that policies are implemented correctly and transparently. Apart from that, HAN also protects community rights through an administrative lawsuit mechanism, providing space for the community to demand justice against detrimental policies. The transparency guaranteed by HAN increases public participation in the policy-making process, improves the quality of policies, and increases the legitimacy of policies in the eyes of the public. Overall, State Administrative Law supports the creation of legal, fair, transparent and accountable public policies, and ensures that people's rights are protected.